Fermentation parameters, antioxidant capacities, and volatile flavor compounds of tomato juice–skim milk mixtures fermented by Lactobacillus plantarum ST-III - Wang, Kun (Food Sci Biotechnol, 2019)
This study evaluated the influence of tomato juice enriched with the probiotic strain Lactobacillus plantarum ST-III on the flavor and health-promoting effects of fermented skim milk. Fermentation parameters, such as titratable acidity, viable cell counts, antioxidant activity, and volatile components, were examined. The viable bacterial cell counts of 40% tomato juice samples were significantly higher than those in the control group, peaking at 1.09 × 10(9) CFU/mL after 48 h, and the titratable acidity was increased by 2.76-fold versus the control value. The antioxidant ability of fermented milk was correlated with the tomato juice content in addition to fermentation time in the 2,2-diphenyl-1-picrylhydrazyl and ferric reducing/antioxidant power assays; for these methods, the scavenging activities of 40% samples were 1.18- and 1.28-fold higher than the control values, respectively, at 24 h. Moreover, abundant flavor components, especially aldehydes, were detected after the addition of L. plantarum ST-III-supplemented tomato juice.